Efficient Multi-Enzymes Immobilized on Porous Microspheres for Producing Inositol From Starch - Han, Pingping; Zhou, Xigui; You, Chun (Frontiers in Bioengineering and Biotechnology, 2020)
In vitro synthetic enzymatic biosystem is considered to be the next generation of biomanufacturing platform. This biosystem contains multiple enzymes for the implementation of complicated biotransformatiom. However, the hard-to-reuse and instability of multiple enzymes limit the utilization of this biosystem in industrial process. Multi-enzyme immobilization might be a feasible alternative to address these problems. Herein, porous microspheres are used as carriers to co-immobilize multiple enzymes for producing inositol from starch. At first, all the enzymes for converting starch to inositol were immobilized on porous microspheres individually to check the effect of immobilization, then all the enzymes are co-immobilized on porous microspheres. Compared to reaction system containing all the individual immobilized enzymes, the reaction system containing the co-immobilized enzymes exhibit ~3.5 fold of reaction rate on producing inositol from starch. This reaction rate is comparable to that by free enzyme mixture. And the co-immobilized multi-enzyme system show higher thermal stability and recovery stability than free enzyme mixture. After 7 batches, the immobilized enzymes retain 45.6% relative yield, while the free enzyme mixture only retain 13.3% relative yield after 3 batches. Co-immobilization of multiple enzymes on porous microspheres for biomanufacturing would shed light on the application of in vitro synthetic enzymatic biosystem in industrial scale.